2015
DOI: 10.1371/journal.pone.0135635
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes and Zooarchaeology at Teotihuacan, Mexico Reveal Earliest Evidence of Wild Carnivore Management in Mesoamerica

Abstract: From Roman gladiatorial combat to Egyptian animal mummies, the capture and manipulation of carnivores was instrumental in helping to shape social hierarchies throughout the ancient world. This paper investigates the historical inflection point when humans began to control animals not only as alimental resources but as ritual symbols and social actors in the New World. At Teotihuacan (A.D. 1–550), one of the largest pre-Hispanic cities, animal remains were integral components of ritual caches expressing state i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 30 publications
0
43
0
2
Order By: Relevance
“…rabbits (Sylvilagus sp. ), white-tailed deer (Odocoileus virginianus), peccaries (Tayassuidae) and large felids (e.g., Puma concolor, Panthera onca) (Corona Martínez 2002a, 2013Hamblin 1984;Lapham, Feinman and Nicholas 2012;Sugiyama, Somerville and Schoeninger 2015;Valadez Azúa 1993, 2003White et al 2004). The extent of these practices is unclear, as is whether the captive animals were maintained for subsistence as well as for elite display and ceremonial purposes, but regardless, Ocellated Turkey husbandry would not be out of place within this cultural framework.…”
Section: Mesoamerican Turkeysmentioning
confidence: 99%
See 2 more Smart Citations
“…rabbits (Sylvilagus sp. ), white-tailed deer (Odocoileus virginianus), peccaries (Tayassuidae) and large felids (e.g., Puma concolor, Panthera onca) (Corona Martínez 2002a, 2013Hamblin 1984;Lapham, Feinman and Nicholas 2012;Sugiyama, Somerville and Schoeninger 2015;Valadez Azúa 1993, 2003White et al 2004). The extent of these practices is unclear, as is whether the captive animals were maintained for subsistence as well as for elite display and ceremonial purposes, but regardless, Ocellated Turkey husbandry would not be out of place within this cultural framework.…”
Section: Mesoamerican Turkeysmentioning
confidence: 99%
“…These dietary shifts may be studied through stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope analysis since these isotopes serve as proxies for paleodiet (Ambrose and DeNiro 1986, Lee-Thorp, Sealy, and van der Merwe 1989, Schoeninger and DeNiro 1984. Isotopic shifts associated with animal husbandry and domestication have been identified previously for Old World taxa including sheep, goats, pigs and cattle (Abarella, Dobney and Rowley-Conwy 2006;Balasse and Ambrose 2005;Makarewicz and Tuross 2012;Minagawa et al 2005;Noe-Nygarrd et al 2005), and in Mesoamerican dogs, deer, rabbits, and captive reared predators (Somerville 2015;Sugiyama, Somerville and Schoeninger 2015;Tykot, van der Merwe and Hammond 1996;White et al 2004). At archaeological sites in the American Southwest, stable isotope analysis has similarly documented rearing of both domestic turkeys (McCaffery et al 2014;Rawlings and Driver 2010) and captive scarlet macaws (Ara macao) (Somerville, Nelson, and Knudson 2010) based on their extensive consumption of maize (Zea mays).…”
Section: Reconstructing Turkey Diet: Stable Isotope Analysis (δ 13 C mentioning
confidence: 99%
See 1 more Smart Citation
“…The higher isotope values in foxes from the east locus could mean that the animals interred there were provisioned and kept for ceremonial purposes. At Teotihuacan in Mexico, some felids (Panthera onca and Puma concolor) intended for sacrifice were first held for several months in captivity, which allowed enough time for bone collagen δ 13 C values to reflect consumption of maize, while other individuals were sacrificed before dietary maize was integrated into this tissue (Sugiyama et al, 2015). These differences may be equivalent to the variability in isotope values from foxes found at a single archaeological site, raising the possibility that some animals were provisioned while others were not, and suggesting that differing cultural practices on the northern and southern islands may have influenced the diet of some late Holocene island foxes.…”
Section: Late Holocenementioning
confidence: 99%
“…Human provisioning of animals is an important step in the domestication process (Axelsson et al, 2013;Barton et al, 2009;Hu et al, 2008;Makarewicz and Tuross, 2012;Zeder, 2006;Zeder et al, 2006) and dietary changes have also been identified in captive and ritually sacrificed animals held by prehistoric peoples (Sugiyama et al, 2015;White et al, 2001). Unintentional or intentional human provisioning of wild animals can impact body condition (Heiss et al, 2009) and the ability of an animal to effectively teach their young how to forage for wild food.…”
Section: Introductionmentioning
confidence: 99%